25. Factors relating to good outcomes after mechanical thrombectomy for acute anterior circulation ischemic stroke within 4.5 Hours from the onset - An, Nguyen Huu; Luu, Vu Đang; Ton, Mai Duy (Tạp chí Nghiên cứu Y học, 2022)
Mechanical thrombectomy (MT) has been accepted as a standard treatment worldwide for patients suffering from acute anterior large vessel occlusion (AC-LVO) who can start early MT within 6 hours. However, in Vietnam, there remains a paucity of information regarding factors that can affect outcomes following this treatment. This study aimed to assess the clinical, imaging, and procedural factors related to good outcomes after MT for patients with AC-LVO within 4.5 hours. We analyzed data from 120 patients at Bach Mai hospital who had acute ischemic stroke (AIS) due to AC-LVO and were treated with MT with and without intravenous thrombolysis (IVT) within 4.5 hours from December 2020 to September 2022. Logistic regression analysis was used to examine the associations of clinical, imaging, and procedural variables with a good outcome. Overall, successful revascularization was achieved in 102/120 cases (85.0%) and 70 patients (58.3%) had a good outcome at 90 days. Successful revascularization (OR, 1.40; 95% CI, 1.24-1.58; p<0.01), initial blood glucose level (OR, 0.86; 95% CI, 0.85-0.87; p=0.046), and hemorrhagic transformation (OR, 0.83; 95% CI, 0.76-0.90; p=0.02) were independent factors associated with good outcome at 90 days.